2005
DOI: 10.1073/pnas.0500312102
|View full text |Cite
|
Sign up to set email alerts
|

Homoserine and asparagine are host signals that trigger in planta expression of a pathogenesis gene inNectria haematococca

Abstract: Some pathogenesis-related genes are expressed in fungi only when the pathogen is in the host, but the host signals that trigger these gene expressions have not been identified. Virulent Nectria haematococca infects pea plants and requires either pelA, which is induced by pectin, or pelD, which is induced only in planta. However, the host signal(s) that trigger pelD expression was unknown. Here we report the isolation of the host signals and identify homoserine and asparagine, two free amino acids found in uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 41 publications
0
35
0
3
Order By: Relevance
“…cDNA prepared from cultured mycelium was diluted 1/100 to compensate for the biomass differences in planta. (59) showed that the pelD gene of Nectria haematococca was expressed in response to homoserine and asparagine, that a specific plant factor responsible for expression of one of these genes was identified. The inability of E. festucae Fl1 to induce lpsB expression in the presence of a plant extract suggests that the inducing factor was not stable or, alternatively, that specific signaling between the epichloë endophyte and the grass host occurs.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA prepared from cultured mycelium was diluted 1/100 to compensate for the biomass differences in planta. (59) showed that the pelD gene of Nectria haematococca was expressed in response to homoserine and asparagine, that a specific plant factor responsible for expression of one of these genes was identified. The inability of E. festucae Fl1 to induce lpsB expression in the presence of a plant extract suggests that the inducing factor was not stable or, alternatively, that specific signaling between the epichloë endophyte and the grass host occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that pathogens specialise to use homoserine as a host signal to trigger the expression of pathogenesis genes (Yang et al, 2005). Also, derivatives of homoserine such as homoserine lactone serve as signal substances involved in microbiological quorum sensing, enabling bacteria to communicate and coordinate behaviour and responses to nutritional status via signalling molecules (Bauer and Mathesius, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These authors used a 31 P-NMR technique that made it possible to discriminate between OPHS in the cytosol and in the chloroplasts based on a shift in the OPHS resonance spectrum caused by different pH-values. Homoserine (or its derivatives) may also function in planta as a host signal for the expression of pathogenesis genes such as pelD in Nectria haematococca (Yang et al, 2005). To gain knowledge of the role of HSK and its possible effect on OPHS levels, especially in the context of cellular compartment, we applied a transgenic approach in potato.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of the latter are cell wall components that induce expression of cell wall degrading enzymes (Huertas-Gonzalez et al, 1999;RuizRoldan et al, 1999;Sexton et al, 2000), phytoalexins that induce the enzymes that can detoxify them (e.g. pisatin demethylase 1) (Straney and VanEtten, 1994), and the amino acids homoserine and asparagine, found in high levels in pea seedling hypocotyls and capable of inducing expression of pelD (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%